Mittag-Leffler-Pade approximations for the numerical solution of space and time fractional diffusion equations - Borhanifar, Abdollah; Valizadeh, Sohrab (International Journal of Applied Mathematical Research, 2015)
Anomalous diffusion and non-exponential relaxation patterns can be described by a space - time fractional diffusion equation. This paper aims to present a Pade approximation for Mittag-Leffler function mixed finite difference method to develop a numerical method to obtain an approximate solution for the space and time fractional diffusion equation. The truncation error of the method is theoretically analyzed. It is proved that the numerical proposed method is unconditionally stable from the matrix analysis point of view. Finally, some numerical results are given, which demonstrate the efficiency of the approximate scheme.